A framework for modelling in-sewer thermal-hydraulic dynamic anomalies driven by stormwater runoff and seasonal effects. (1st February 2023) - Figueroa, Alejandro; Hadengue, Bruno; Leitão, João P.; Blumensaat, Frank
Highlights: We offer a framework to model thermal-hydraulic dynamics across the urban water cycle. The framework can simulate thermal shocks of rainwater in combined sewers. In-sewer temperature dynamics across seasons are validated against measurement data. We quantify the impact of decentralized HR on WRRF heat budgets during wet weather. Abstract: Rain-induced surface runoff and seasons lead to short- to medium-term anomalies in combined storm- and wastewater flows and temperatures, and influence treatment processes in wastewater resource recovery facilities (WRRF). Additionally, the implementation of decentralized heat recovery (HR) technologies for energy reuse in buildings affect energy-related processes across the urban water cycle and WRRFs heat inflows. However, quantitative insights on thermal-hydraulic dynamics in sewers at network scale and across different scales are very rare. To enhance the understanding of thermal-hydraulic dynamics and the water-energy nexus across the urban water cycle we present a modular framework that couples thermal-hydraulic processes: i) on the surface, ii) in the public sewer network, iii) in households (including in-building HR systems), and iv) in lateral connections. We validate the proposed framework using field measurements at full network scale, present modelling results of extended time periods to illustrate the effect of seasons and precipitation events simultaneously, and quantify the impact of decentralized HR devices on thermal-hydraulics. Simulation results suggest that the presented framework can predict temperature dynamics consistently all year long including short- to long-term variability of in-sewer temperature. The study provides quantitative evidence that the impact of household HR technologies on WRRF inflow heat budgets is reduced by approximately 20% during wet-weather periods in comparison to dry-weather conditions. The presented framework has potential to support multiple research initiatives that will improve the understanding of the water-energy nexus, pollutant dispersion and degradation, and support maintenance campaigns at network scale. Graphical abstract: Image, graphical abstract